HUBUNGAN STATUS GIZI, STATUS IMUNISASI, DAN ASI EKSKLUSIF DENGAN KEJADIAN ISPA PADA ANAK BALITA - Fransiska, Mellia; Rina, Rina; Okta Sanggara, Vivi; Kurnia Gustin, Rahmi (LPPM Universitas Prima Nusantara Bukittinggi, 2015)
Acute Respiratory Infections (ARI) is an acute infections process which incubation for 14 days. It’s caused by microorganisms and attack one or more of the airway. Tanah Datar is a regency that incidence of ARI in children toddlers was highest (80.65%) in West Sumatera in 2011, with the most case in Batipuh I Health Centre (123.47%). The aims of this study were known variable and dominant factor relationship of ARI incidence on children toddlers at working area of Batipuh I Health Centers. Design of this research was cross sectional. Population was all mothers who have children toddlers (2079 people) and obtained 106 sample with multistage sampling technique. Data were analyzed by univariate and bivariate with Chi-square test. The results showed that there was a significant association between immunization status (p = 0.006, OR=6588, CI = 95%) and exclusive breastfeeding (p = 0.015, OR = 2.985, CI = 95%). Recommended to Batipuh I Health Center to provide information about the importance of immunization, exclusive breast feeding, and monitoring the nutritional status of children toddlers. The parents should provide a complete immunization, exclusive breast feeding, and pay attention to the nutritional status of children toddlers in order to anticipate the incidence of ARI.